'Enter the Dream Tiger'. Borges, Abbau and the Shrouded Hall of Mirrors of Educational Reflection. Issue 1 (May 2022) - Hodkinson, Alan
This article reflects upon initial teacher education programme's employment of reflection. The article argues that the orginary ground of educational reflection, dominated by theorists such as Dewey and Schon, has been colonised by a form of 'Total Reflection' that is conceptualised and manufactured within the Teacher Standards and its associated discourse. Through employment of the concept of Abbau, the work of Borges and mirror theory, the article reveals how student teachers are not enabled to be reflective but instead are created as the celebrated automata whose professional image is shrouded, codified and solidified by a Master Weaving machine. The article suggests that if educational reflection is to become useful in teacher development, then it must return to its past incarnations.